Forecasting and prognosing in education - Pitula, Beata (DIAGNOSTIKA A PORADENSTVÍ v pomáhajících profesích, 2019)
Predicting future events and processes based on the existing in the past authentic social events allow today to make a statement that in many areas of life the issue of forecasting begins to play a very important role. Most frequently it allows to predict certain events or facts, but one cannot resist the impression that a complete surrender to a prognosis is associated with a certain skepticism in assessing the accuracy of “events within the same science as well as outside of it” [1]. It is easy to notice that attempts to obtain reliable knowledge about the future within a certain science encounter numerous theoretically described and empirically confirmed difficulties. These difficulties are manifested with the greatest strength in the so-called issue of prognostic accuracy[2]. [1] A. Kołodziej, Prognozowanie zjawisk społecznych w obrębie socjologii – nadzieje, możliwości, ocena trafności, [in:] I. Sobieraj, A. Kołodziej (ed.), Prognoza, interwencja i ewaluacja w naukach społecznych. Teoria socjologiczna i praktyka badawcza, Wydawnictwo „Adam Marszałek”, Toruń 2015, s.19 [2] Ibidem, p.13